Organic Fertilizer Use Strategy in Corn Farming in Ulu Ere, Bantaeng - Sahlan; Ratnawati Tahir; Zulkifli; Syafiuddin Saleh (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to analyze the strategy of organic fertilizer use in corn farming in Ulu Ere District, Bantaeng Regency. The study involved eight farmers, two extension workers from the Department of Agriculture, and two consumers of mustard greens who used organic fertilizer as informants. Data were collected through in-depth interviews and a SWOT analysis to assess the internal and external conditions in the use of organic fertilizer. The results showed that the external value (opportunities and threats) was at 2.76, while the internal value (strengths and weaknesses) reached 2.92. The proposed strategy is to increase socialization regarding the use of organic fertilizer, reduce dependence on chemical fertilizers, and increase farmers' knowledge and skills in the use of organic fertilizers. This is expected to help farmers reach export markets and improve land management systems for sustainable agriculture. Organic fertilizer is considered to have great potential to improve the quality and productivity of corn farming in Ulu Ere District, while supporting agricultural sustainability.